The Influence of Organizational Culture and Teamwork on Employee Performance with Organizational Commitment as a Indicator Intervening Variables at Representative Offices Bank Indonesia Riau Islands Province - Kamaruzaman; Mesra B; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study focuses on assessing how Organizational Culture and Teamwork influence Employee Performance, with Organizational Commitment as a mediating variable at a Bank Indonesia Representative Office located in the Riau Islands Province. A quantitative methodology was employed, and data analysis was conducted using Structural Equation Modeling (SEM) using SmartPLS 3.0. The study sample consisted of all personnel at the office, selected through a census method. The results indicate that Organizational Culture and Teamwork have a significant positive impact on Employee Performance and Organizational Commitment. Furthermore, Organizational Commitment also exhibits a significant positive effect on Employee Performance. Analysis of the indirect effect indicates that Organizational Commitment significantly mediates the effect of Organizational Culture on Employee Performance, but does not mediate the effect of Teamwork on Employee Performance. These results highlight that improving organizational culture and promoting effective teamwork are important factors for enhancing employee commitment and performance in the banking sector.